Visceral pigmentation in four Dendropsophus species (Anura: Hylidae): Occurrence and comparison - Franco-Belussi, Lilian [UNESP]; de Souza Santos, Lia Raquel; Zieri, Rodrigo [UNESP]; de Oliveira, Classius [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
Amphibians share with other ectothermic vertebrates an extracutaneous pigmentary system consisting of melanin-containing cells in various organs and tissues. This paper describes the interspecific variation in the visceral pigmentation and extracutaneous pigment system in four species of the genus Dendropsophus [i.e., D. elianeae, D. minutus, D. nanus, and D. sanborni (Anura: Hylidae)]. Fifteen adult males from each species were collected in the region of Sao Jose do Rio Preto (State of São Paulo, Brazil), and their visceral pigmentation was analyzed during the reproductive period. The individuals were weighed and measured, and the pigmented visceral cells were classified and documented in photographs.. The shape and quantity of the pigment cells differed among the various structures of the same individual, as well as among the same structures of different species. Similarities and differences among these species were observed, and a visceral pigmentation pattern for anatomical structures was detected. In the digestive system of all species analyzed, there was an absence of pigment cells on the stomach and middle intestine. However, the pigmentation of the final portion of the intestine (i.e., the rectum) showed interspecific variation, with D. minutus presenting intense pigmentation, whereas the other species presented no pigmentation. Significant differences were detected also in the cardio-respiratory system, mesentery, and lumbosacral peritoneum. Crown Copyright (C) 2010 Published by Elsevier GmbH. All rights reserved.
Keywords: Anurans; Extracutaneous pigmentary system; Melanocytes